The Exact Morphology of the Species Ephemera pieli Navás, 1934 from Eastern China (Ephemeroptera: Ephemeridae) - Li, Meng-Yao; Deng, Mu-He; Zhou, Chang-Fa (Zootaxa, 2023)
The original description and outline figure of the mayfly Ephemera pieli Navás, 1934, were based on male subimagoes, and its morphology and taxonomic status have not been confirmed since then. However, recently collected materials from eastern China, including all stages of this mayfly, reveal several unique characteristics that indicate E. pieli is a valid species in the subgenus Ephemera (Ephemera). These characteristics include forewings with numerous dark dots, hindwings or hind wingpads with one or two distinct median dots, penes covered mostly by the subgenital plate, and the apex of the penis bluntly extended. A neotype is designated.